2021
DOI: 10.5114/wiitm.2021.105731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term outcomes of robotic-assisted and laparoscopic-assisted D2 gastrectomy for gastric cancer: a meta-analysis.

Abstract: Aim The aim of the study was to compare the outcomes of robot-assisted (RAGD2) and laparoscopy-assisted gastrectomy with D2 lymphadenectomy (LAGD2) for patients with gastric cancer. Material and methods Relevant articles published up to September 2020 were searched. The weighted mean difference (WMD) was used to pool continuous variables, while risk ratio (RR) was calculated for dichotomous outcomes. Results RAGD2 required a longer operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Analysis involved all 224 studies: out of them, 193 ones turned as not relevant for title and abstract, while 31 full-texts were considered eligible. Twe of the 31 studies were excluded because they were identified as duplicate publicati After removal of 4 studies not complying with inclusion criteria (1 robotic gastrecto versus open gastrectomy meta-analysis; 1 umbrella review; 1 umbrella review protoc network meta-analysis), 7 meta-analyses underwent qualitative synthesis [14][15][16][17][18][19][20]. No ditional record was found through other source (References list).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis involved all 224 studies: out of them, 193 ones turned as not relevant for title and abstract, while 31 full-texts were considered eligible. Twe of the 31 studies were excluded because they were identified as duplicate publicati After removal of 4 studies not complying with inclusion criteria (1 robotic gastrecto versus open gastrectomy meta-analysis; 1 umbrella review; 1 umbrella review protoc network meta-analysis), 7 meta-analyses underwent qualitative synthesis [14][15][16][17][18][19][20]. No ditional record was found through other source (References list).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Table 1 shows demographic features of 7 included meta-analyses that covered 2000-2020 time frame [14][15][16][17][18][19][20]. Studies included into the meta-analyses ranged from 12 to 40, were almost all retrospective ones and originated from Asian countries (China and Korea, in particular) [14][15][16][17][18][19][20].…”
Section: General Population Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations